Metastatic Ovarian Tumor from Incidental Renal Cell Carcinoma: A Case Report and Literature Review - Shaymaa Khalid Abdulqader; Yousif Ayad Abduljabbar Al-Ani; Nabeeha Najatee Akram; Wassan Nori; Mortadha Al-Kinani (Al-Anbar Medical Journal)
Renal cell carcinoma (RCC) is the most common solid lesion within the kidney and accounts for most kidney malignancies. The primary tumor size primarily determines the risk of metastasis in RCC. Literature rarely describes metastasis in tumors less than 2 cm; in fact, around 1/3 of RCC reported cases had metastatic disease at the time of diagnosis. RCC tends to metastasize to the lung in half of the patients, to the bones or the liver in 1/3 of patients, and the brain in 5% of all cases. RCC can metastasize to almost every organ in the human body. However, their metastases to the ovaries are incredibly uncommon. In this report, we describe a female presented with the smallest RCC (1cm) that metastasized to the ovary in a patient with previously undiagnosed autosomal dominant polycystic kidney disease (ADPKD). This case report aimed to raise physicians' awareness of the possibility of metastasis in RCC regardless of tumor size and that metastatic RCC could be the first presentation of patients with ADPKD.